Determinants Of Audience To Attend Comic Book Film Adaptation : A Study Case At Lotus Five Star, Kota Samarahan - Tiang, Li Min (Universiti Malaysia Sarawak (UNIMAS), 2016)
The purpose of this research is to identify the influence factor that determine the audience to attend comic book film adaptation. This research employs uses and gratifications theory to conduct an audience analysis on comic book film adaptation. As we know, this theory has not yet particularly been applied to this genre, thus providing a basis for the research study. A set of self-administered questionnaire were handed out to 250 respondents who attended screening of "Batman Vs Superman: Dawn of Justice" at Lotus Five Star Cinema, Kota Samarahan. By using the data collected from the respondents, the factor was identified by using principal component analysis. Prior to that, descriptive statistic carries out to determine highest category of respondent's attendance. Most of the filmgoers influenced by psychological need, excitement, self-recognition, social fulfillment, and personal development as motivations to attend. The study's limitations and future research directions are discussed.